'We are helpless, we are not the authority': colonial governmentality in a Sri Lankan transnational education institution. Issue 8 (17th November 2022) - Golding, David
ABSTRACT: This study examines colonial governmentality in a Sri Lankan partner institution of University of London (UOL) through semi-structured interviews with students and faculty. UOL began administrating colonised educational spaces in the 19th century, and now governs approximately 80 partner institutions throughout the global South. Its governmentality structures an arterial topology of power that grants limited inclusion to students while excluding their lecturers from formal recognition. Faculty at partner institutions do not assess students. Instead, assessment consists of annual British examinations, effectuating rote pedagogies that centre European knowledge. This extraction of faculty authority shapes delegitimated and disempowered subjectivities. The same process augments UOL's expertise on Southern educational spaces, contributing to a broader project of universalising Western epistemology. The findings suggest a need for further research that examines colonial governmentality in international education, and particularly its mechanisms of epistemic extraction.